Spirituality of HIV-infected female patients treated in a secondary care hospital in Thailand: a preliminary investigation - Natawan Khumsaen; Panarat Chenchob; Supannee Peawnalaw (HIV & AIDS Review. International Journal of HIV-Related Problems)
Introduction Globally, acquired immune deficiency syndrome (AIDS) and human immunodeficiency virus (HIV) infection are major public health concerns. As women experience HIV infection, it is important for them to find meaning in their lives. It is increasingly agreed in literature that spirituality play an important role in life, and has a significant impact on complexity of living of HIV-infected female patients.